(3EYQGH GdaGJMIs
(3ChdgG (B:s
(3CeG HYO, aCbSGe GdcdGe KdGKI(B: (3GSe haYd hMQa dCf GdYHGQI Ydi MSH GdeYHQ Yfg s
(3BNQgG (B:s
(3aGdWQb KdGKI Yde HdG Yed, hgh WQjb GdjghO Je EYQGH GdaGJMI s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B24 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdCRgQ (B(20985) s
Keywords: (3GdfMhs